Clinical Characteristics of COVID-19-Infected Cancer Patients in Pakistan: Differences Between Survivors and Non-Survivors - Asghar, Kashif; Abu Bakar, Muhammad; Akram, Muhammad Junaid; Farooq, Asim; Siddique, Kashif; Rana, Iftikhar Ali; Ali, Jamshed; Rashid, Muhammad Usman; Khan, Ashraf Ali; Loya, Asif (Frontiers in Oncology, 2021)
Background: Cancer patients are considered as highly vulnerable individuals in the current COVID-19 pandemic. We studied the clinical characteristics of survivor and non-survivor COVID-19-infected cancer patients in Pakistan. Patients and Methods: We did a retrospective study of 70 cancer patients with PCR-confirmed COVID-19 infection from Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore and Peshawar, Pakistan between April 13 and July 09, 2020. These patients were discharged from the hospital or had died by July 09, 2020. Clinical, pathological and radiological characteristics were compared between survivors and non-survivors by fisher’s exact test and chi-square test. Univariable and multivariable logistic regression models were performed to explore the risk factors of mortality. Results: Seventy cancer patients with SARS-CoV-2 infection were enrolled and majority were males 38 (54.3%). 57 (81.4%) had solid tumors and 13 (18.6%) had hematological malignancies. Dyspnea (44 cases) was the most common symptom (62.9%). Complications were reported in 51 (72.9%) patients; during the course of disease. 19 (27.1%) patients were admitted to an intensive care unit (ICU). A significant increase in the C-reactive protein level and neutrophil count was observed in the deceased patients as compared to the surviving patients. D-dimer values of ≥0.2 mg/L were significantly associated with mortality (P=0.01). We identified two independent risk factors associated with death, ICU admission (P=0.007) and D-dimer (P=0.003). Conclusion: Pakistani cancer patients with COVID-19 infection reported poor prognosis. Intensive surveillance of clinicopathological characteristics of cancer patients infected with COVID-19 especially D-dimer values may play a pivotal role in the outcome of disease.